Number of prior live births is associated with higher arterial stiffness but not its change in older women: the atherosclerosis risk in communities study - Bonner, Alison N.; Jayawickreme, Shantal; Malek, Angela M.; Vladutiu, Catherine J.; Oliver-Williams, Clare; Cortés, Yamnia I.; Tanaka, Hirofumi; Meyer, Michelle L. (Frontiers in Cardiovascular Medicine, 2023)
Introduction Although studies have demonstrated a J-shaped association between parity and cardiovascular disease (CVD), the association with arterial stiffness is not fully understood. Methods We examined the association between parity and carotid-femoral pulse wave velocity (cfPWV), a measure of central arterial stiffness. We conducted a longitudinal analysis of 1220 women (mean age 73.7 years) who attended the Atherosclerosis Risk in Communities Study visit 5 (2011-2013). At visit 2 (1990-1992), women self-reported parity (number of prior live births), which we categorized as: 0 (never pregnant or pregnant with no live births); 1-2 (referent); 3-4; and 5+ live births. Technicians measured cfPWV at visit 5 (2011-2013) and visit 6 or 7 (2016-2019). Multivariable linear regression modeled the associations of parity with visit 5 cfPWV and cfPWV change between visit 5 and 6/7 adjusted for demographics and potential confounding factors. Results Participants reported 0 (7.7%), 1-2 (38.7%), 3-4 (40.0%), or 5+ (13.6%) prior live births. In adjusted analyses, women with 5+ live births had a higher visit 5 cfPWV (β=50.6 cm/s, 95% confidence interval: 3.6, 97.7 cm/s) than those with 1-2 live births. No statistically significant associations were observed for other parity groups with visit 5 cfPWV or with cfPWV change. Discussion In later life, women with 5+ live births had higher arterial stiffness than those with 1-2 live births, but cfPWV change did not differ by parity, suggesting women with 5+ live births should be targeted for early primary prevention of CVD given their higher arterial stiffness at later-life.